Prohibition of Adoption Involving Foreigners and Stateless Persons Under Martial Law - Rudenko, Oksana; Pavliuk, Anna (Problems of legality, 2025)
The relevance of the topic is due to the need to consider the issue of the peculiarities of legal protection of children’s interests in the conditions of the legal regime of martial law in Ukraine and the definition of the specifics of legal regulation of public relations of adopting with a foreign element during the war. The article describes the limitations on the possibility of adoption of children by foreigners in Ukraine under martial law. It is noted that adoption is carried out, first of all, in the interests of the child to ensure stable and harmonious conditions for his/her life. The purpose of the article is to reveal the legal nature of interstate adoption by foreigners or citizens of Ukraine living outside its borders. The achievement of the outlined goal became possible due to the use of a complex of methods of scientific knowledge, in particular, philosophical, general scientific and special ones based on synthesis, analysis, induction and deduction. The article points out the need to comply with the adoption procedure and control over the living conditions of the child. The study analyzes the main tasks of the National Social Service of Ukraine as a central executive body, whose activities are directed and coordinated by the Cabinet of Ministers of Ukraine through the Ministry of Social Policy and implements state policy in the field of protecting children’s rights. It was concluded that adoption of children by citizens of other countries is temporarily impossible due to the fact that the National Social Service, which manages issues of intercountry adoption and issues of permission for adoption, is temporarily not considering adoption cases. Based on the results of the conducted research, in order to avoid any future differences in law enforcement approaches, separate proposals were made for the proper regulation of the issue of conducting the adoption procedure with a foreign element under martial law in Ukraine.